Manajemen Strategi Kepala Madrasah dalam Meningkatkan Kompetensi Profesionalitas Guru di MAN 1 Pringsewu - Mustafida (CV. Creative Tugu Pena, 2024)
This research aims to analyze the strategic management of madrasa heads in improving the professional competence of teachers at MAN 1 Pringsewu. Teachers' professional competence supports the success of the educational process, especially in meeting national education standards. This research approach uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation. The research results show that the madrasa head at MAN 1 Pringsewu implements three main strategies: (1) planning training and development programs, (2) implementing routine academic supervision, and (3) building a collaborative work culture among teachers. This strategy is effective in increasing teacher competency, as proven by increasing student achievement and learning quality.